Efektivitas Layanan Bimbingan Kelompok terhadap Keterampilan Pemanfaatan Waktu Luang yang Efektif dan Efisien Siswa di SMK - Elviana; Arjoni; Sekar Kinasih Khairiyah; Yeni Afrida (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
This research is motivated by a problem at SMK N 1 Baso, namely that students are unable to utilize their free time productively. Group guidance services can help improve these skills. This study aims to determine the effectiveness of group guidance on students' free time utilization skills. The method used was a pre-experimental design with a one-group pre-test post-test on eight students selected through purposive sampling. The research instrument was a Likert scale questionnaire. Data analysis used the Shapiro-Wilk test and the Wilcoxon Signed Rank Test with SPSS 26. The results showed a Sig. 0.011 <0.05, indicating that group guidance is effective in improving students' free time utilization skills.